(3QjMGfI GdcJGH hfLYI GdefJGHs - (3CHhYHO Gddg eMeO Hf YHO Gddg Hf SYjO GdSdeGfi GdZQfGWi GdCfOdSj, GdTgjQ HdSGf GdOjf Hf GdNWjH,J (B776 (3g` s
(3ChdgG (B:s
(3eHJhQ, hGhd GdehLhO ajgG(B: (3fSCd Gddg Cf jOaY YfG hYfce YhGOi GdaJf hZhGFd GdeMf hjLYdfG Ydi SfI GdfHjjf hjdHSfG ef JbhGg Ch ai GdLff s
(3BNQgG (B:s
(3hGLYd hcOc ai GMJQGSc , heMh eQGSc s
(3GdLRA GdChd bWYI ef CNQgs
(3fSNI KGefIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B605 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B61 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs